A multicenter, randomized, double‐blind placebo‐controlled, single dose trial of the safety and efficacy of intravenous ibuprofen for treatment of pain in pediatric patients undergoing tonsillectomy. Issue 5 (20th March 2014) - Moss, Jonathan R.; Watcha, Mehernoor F.; Bendel, Laima P.; McCarthy, Denise L.; Witham, Stacy L.; Glover, Chris D.; Lonnqvist, Per‐Arne
Summary Background Tonsillectomy is one of the most common pediatric procedures in the United States. An optimal perioperative pain control regimen remains a challenge. Intravenous ibuprofen administered at induction of anesthesia may be a safe and efficacious option for postoperative tonsillectomy pain. Objectives To determine whether preoperative administration of intravenous ibuprofen (IV‐ibuprofen) can significantly decrease the number of doses of postoperative fentanyl when compared with placebo in pediatric tonsillectomy surgical patients. Methods This was a multicenter, randomized, double‐blind placebo‐controlled trial conducted at six hospitals in the United States. A total of 161 pediatric patients aged 6–17 years undergoing tonsillectomy were randomized to receive either a single preoperative dose of 10 mg·kg−1 IV‐ibuprofen or placebo (normal saline). Postoperative pain was managed with intravenous fentanyl (0.5 μg·kg−1) on an as needed basis when the visual analog scale (VAS) was >30 mm and deemed appropriate by recovery room nurse/physician. The primary endpoint was the number of doses and amount of postoperative fentanyl administered postoperatively for rescue analgesia. Results There was a significant reduction in the number of postoperative doses and the amount of fentanyl administered after surgery in the IV‐ibuprofen group compared with the placebo group (P = 0.021). There were no differences in the time to first analgesia request or the number of patients who required postoperative analgesia. There were no significant differences in the incidence of serious adverse events, surgical blood loss (P = 0.662), incidence of postoperative bleeding, or a need for surgical re‐exploration between the treatment groups. Conclusion Administration of IV‐ibuprofen, 10 mg·kg−1, significantly reduced fentanyl use in pediatric tonsillectomy patients.